Rational use and cost variation analysis of antitussive-expectorants available in the Indian market: a pharmacoeconomic study - Manjhi, Pramod Kumar; Singh, Sunil Kumar; Kumar, Chakrapani; Rana, Akhilesh Kumar (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Antitussive-expectorants are among the most frequently prescribed drugs by physicians in clinical practice. Upper respiratory tract infections, such as common cold, acute pharyngitis and acute trachea-bronchitis, are the most common of all communicable diseases and significantly increase OPD burden. This study aimed to assess the rational use, cost ratio, and percentage cost variations in different brands of the commonly prescribed antitussive-expectorants available in the Indian market. Methods: The cost of antitussive-expectorant manufactured by different pharmaceutical companies was obtained by using drug today Jan-April 2021 vol 2. The maximum and minimum price was noted down, cost ratio and percentage cost variation of the individual formulation were analysed. Results: Analysis of cost ratio and percentage cost variation for each formulation of the antitussive-expectorants drug, syrup (100 ml) chlorpheniramine (2 mg), dextromethorphan (10 mg), phenylephrine (5 mg) combinations show the highest cost ratio and percentage cost variation as 5.30 and 430.25 respectively, and syrup (100 ml) dextromethorphan (10 mg), guaifenesin (100 mg), phenylephrine (25 mg), chlorpheniramine (4 mg) combinations show lowest cost ratio and percentage cost variation as 1.17 and 17.69 respectively. Conclusions: There was a wide variation in the cost of different brands of antitussive-expectorant drugs available in the Indian market. So, clinicians should be aware of rational use and variations in cost to reduce the treatment cost and increase patient compliance.